Perspectives Of The Diagnostic And Development Of Art Endowments And Art Disciplines’ Future Teachers - A. Kolchanova, Elena; O. Shohov, Konstantin; S. Demin, Gregory (Opción, 2019)
The research’s relevance is determined by the importance of assessing the trans- formation of methods of artistic teaching in the Soviet and post-Soviet period, as well as searching for effective methods for diagnosing the artistic endowments of young people, which determines the perspectives of the development of high art education, and as a result the professional qualities of future art teachers. In this connection, this article is aimed at revealing the main characteristics of artistic endowments, developing a system of exercises-tests. It helps to identify artistically gifted and talented students. The leading approach to the study of this problem is the introduction in the academic process of the university of a set of effective methods, such as acceleration (a technique aimed at accelerating the development of acquired artistic skills); (method of complication of compositional, graphic and pictorial tasks) and enrichment (the method of inclusion in an active artistic group activity.) The article presents a diagnostic tool on the basis of which the main com- ponents of the student’s artistic talent are revealed, recommendations on work with artistically gifted youth in higher education. The materials of the article are of practical value for teachers in the field of art education.